Ontology Modeling of The Nymphalidae Family Butterfly on Java Island Using the Methontology - Nurbojatmiko, Nurbojatmiko; Yusri, Azizah Nurfauziah; Sulasiyah, Ismi Ana; Wulandari, Winda (Applied Information System and Management (AISM), 2025)
Indonesia, a mega-biodiverse nation with 53 national parks, including 12 on Java Island, hosts an immense variety of flora and fauna, particularly within the Nymphalidae butterfly family. However, the country's vast geographical complexity makes the understanding, classification, and management of information about these butterflies highly challenging, leading to fragmented and difficult-to-process data. This research aims to address this problem by constructing an ontology-based knowledge base to enable effective information reuse, integration, and semantic processing of Nymphalidae butterfly data from Java's national parks. The methodology employed the Methontology framework, which structured the development process into detailed stages: specification, conceptualization, formalization, implementation, and maintenance. The ontology was formally built using the Web Ontology Language (OWL) and the Resource Description Framework (RDF), with development and implementation carried out using the Protégé tool. Data integration and querying were facilitated through the application of semantic web standards, including SPARQL for retrieving information. The results yielded a structured semantic model for Nymphalidae butterflies in Java, comprising 7 classes, 4 object properties, and 4 data type properties. A critical evaluation using the HermiT Reasoner confirmed the ontology's logical consistency, proving the model to be sound. The primary contribution of this study is a validated, interoperable ontology that provides a standardized framework for organizing butterfly information, thereby facilitating better data sharing, integration, and knowledge management for biodiversity conservation and research efforts in Indonesia.